Analisis Komprehensif: Perbandingan Platform Perangkat Lunak Artificial Intelligence (AI) untuk Meningkatkan Inovasi dalam Desain Interior - Tahsin, Muhammad; Afkar, Muhammad Agha (Journal of Engineering and Science, 2023)
This research aims to conduct a comparative study of artificial intelligence (AI) software platforms used in interior design. The focus of the study is to evaluate the effectiveness, sophistication, and performance of various AI platforms in supporting innovation and efficiency in the internal design process. This research method involved an in-depth analysis of several leading AI platforms used in interior design, reviewing their superior features, personalization capabilities, and integration with other design tools. In addition, this research will evaluate the impact of using these platforms on project completion time, design results accuracy, and client satisfaction. The results of this research can provide valuable insight for interior design professionals. By understanding how AI platforms compare, professionals can make more informed decisions in selecting the solution that best suits their project's needs. In an era of rapid technological development, this research can provide helpful guidance for optimally utilizing AI technology, thereby achieving interior design results that are not only innovative but also efficient. The conclusions from the research can provide beneficial advice in optimally utilizing AI technology to achieve innovative and efficient interior design results. By identifying the strengths and weaknesses of each platform, interior design professionals can optimize the use of AI technology according to their project needs and preferences. As a result, this research can positively contribute to the development of the interior design industry, creating a more productive and satisfying work environment for professionals and clients.